Advances in therapy in newborns - Dobrzańska, Anna; Gołkowska, Małgorzata; Gruszfeld, Dariusz; Czech-Kowalska, Justyna (Przewodnik Lekarza/Guide for GPs, 2009)
Birth asphyxia is the most common cause of morbidity and mortality in newborns and the most common risk factor for intracranial haemorrhage and periventricular leucomalacia. Prevention of asphyxia and its consequences is the challenge for neonatology of the twenty-first century.